The long-term effects of school dropout and GED attainment on substance use disorders. (1st January 2016) - Reingle Gonzalez, Jennifer M.; Salas-Wright, Christopher P.; Connell, Nadine M.; Jetelina, Katelyn K.; Clipper, Stephen J.; Businelle, Michael S.
Highlights: Dropouts were more likely to smoke and have a marijuana use disorder in adulthood. Attainment of a GED does not appear to be protective from substance use. Those with a GED were more likely to smoke than dropouts or graduates. Participants with a GED had more marijuana use disorders than graduates. Dropouts were more likely than graduates to initiate smoking in high school. Abstract: Background: Epidemiologic research suggests that 14% of the population do not complete high school, and dropout has been linked to mental health conditions, substance use, chronic health problems, and criminal behavior. Few studies have assessed whether attainment of the general education development (GED) credential is protective from substance use. Purpose: To assess the long-term outcomes of school dropout and GED attainment on past year substance use disorders, age of onset, and current smoking status. Methods: Longitudinal data were included for lifetime substance users who participated in the National Epidemiological Survey on Alcohol and Related Conditions (Waves I and II). Eligible participants ( N = 30, 608) were classified as having completed high school, dropped out of high school and did not complete a GED, or completed GED at Wave I. Survey logistic regression analyses were used to determine whether high school graduation status was associated with substance use disorders and smoking at Wave II. Results: Multivariate results suggest that participants who dropped out of high school (OR = 1.53; p < .01) or attained a GED were more likely to have a past year marijuana use disorder (OR = 1.62 p < .01) compared to high school graduates. High school dropouts were also more likely to be current smokers (OR = 1.88; p < .05) than graduates. Conclusions: High school dropouts have higher long-term rates of marijuana use disorder and smoking in adulthood than graduates. Attainment of a GED does not appear to be protective from marijuana use disorders in adulthood.